Household Food Security of Rice Farmers Based on Food Expenditure and Energy Consumption in Singaran Pati Sub-District, Bengkulu City - Ifebri, Rihan; Wibowo, Hariz Eko; Fauzi, Ariffatchur; Nolasary, Mega Putri (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
This study was conducted in the Singaran Pati Sub-district of Bengkulu City to analyze food expenditure shares, energy consumption, and household food security levels among rice-farming households. A descriptive-analytical method was employed, with research sites selected purposively and samples determined proportionally, resulting in 63 respondents from Dusun Besar and 34 from Panorama. Both primary and secondary data were utilized. Food expenditure share was calculated based on the ratio of food to total household expenditure, while energy consumption was assessed using a one-sample t-test. Food security status was measured by cross-classifying food expenditure share and energy consumption. The results show that the food expenditure share reached 80.98%, indicating a high category, while energy consumption was 97.38%, categorized as sufficient. Overall, most rice-farming households were classified as food-insecure.